An ergodic approach to Pötzsche–Siegmund–Wirth's region of exponential stability. (May 2020) - Jackson, Billy J.; Davis, John M.
Abstract: We present a new technique for calculating the Pötzsche, Siegmund, and Wirth's region of exponential stability for a time scale, S ℂ ( T ) . The approach taken here unifies and extends other results on this topic in the literature. We establish a tractable algorithm for computing S ℂ ( T ) in terms of the asymptotic extended graininesses of the time scale and their relative frequencies.